Responsibility of performing puja - Mumbai Archive Project Team (Jio Institute, 2024)
The women in the household are often responsible for offering puja. Rituals involve watering the plant, purifying the space around the plant with water and cow dung, and making offerings of food, flowers, incense, gangajal (water of the River Ganga), etc. In the evening, arati (the ritual of offering the sacred fire) is conducted around the Tulsi plant.